Pengaruh internal locus of control terhadap perilaku altruistik - William Yosua Theofani Sutiadi; Agustin Rahmawati; Al Thuba Septa Priyanggasari (Jurnal Psikologi Tabularasa, 2020)
Altruistic behavior is currently experiencing a lot of decline and tends to fade away. Globalization is marked by the rapid development of technology and communication, which makes many individuals look selfish and ignores and decreases empathy for others. The purpose of this research is to analyze the influence of internal locus of control on altruistic behavior in students. This type of research uses a quantitative approach. The results of the calculation of the correlation coefficient value of 0.660 with a significance value of 0.000 (p 0.05). These results show a positive relationship between internal locus of control and altruistic behavior. The contribution of internal locus of control to altruistic behavior is 43.5%, while the influence of other factors is 56.5%. Suggestions for further research is to associate altruistic behavior with other variables and use samples other than students.